If you would like to factor completely 3 * x^2 - x - 4, you can do this using the following steps:
<span>3 * x^2 - x - 4 = (3 * x - 4) * (x + 1) = (3x - 4) * (x + 1)
</span>
The correct result would be (3x - 4) * (x + 1<span>).</span>
Answer: y= -3x+4
Step-by-step explanation:
Hope this helps
Answer:
Yes, she is correct.
Step-by-step explanation:
y = kx is direct variation
15 = k*-3
k = -5.
So the equation of variation is
y = -5x
When x = -4:
y -5*-4 = 20.
Answer and explanation:
Probability = number of favorable outcomes/ total number of outcomes
Since all glasses labelled C, D, and P are all same Cola
Probability that C is ranked first = 1/3
Probability that D is ranked last = 1/3